2008
DOI: 10.1002/cjce.5450830225
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation and Prediction of Butane/Water and Gas/Butane Partition Coefficients

Abstract: It has been pointed out previously that the butane/water partition coefficient is a key parameter in the determination of extraction affinity. We have taken 43 such partition coefficients and have obtained a very satisfactory correlation with Abraham solvation parameters. Similarly, we have obtained a good correlation of 43 gas/butane partition coefficients. These correlations are general, and can be used to predict further values of the butane/water and gas/butane partition coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Specifically, there is no hydrate or solvate formation, and that for compounds that exhibit polymorphism, the same polymorph exists in both phases, (b) the secondary medium activity coefficient of the solute in the two phases is near unity (in practice, this means that the solute should not be too soluble), and (c) the equation refers to the same chemical species in each phase; thus for ionisable species, it will be the un‐dissociated form. We have already shown that partition coefficients between water and a large number of phases can be predicted through a series of linear free energy equations, LFERs,26–44 so that if S w is known, then S s can be predicted for the various phases. The method is very general, because the phases include wet (water‐saturated) organic solvents, dry organic solvents, ionic liquids and aqueous biphasic systems.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, there is no hydrate or solvate formation, and that for compounds that exhibit polymorphism, the same polymorph exists in both phases, (b) the secondary medium activity coefficient of the solute in the two phases is near unity (in practice, this means that the solute should not be too soluble), and (c) the equation refers to the same chemical species in each phase; thus for ionisable species, it will be the un‐dissociated form. We have already shown that partition coefficients between water and a large number of phases can be predicted through a series of linear free energy equations, LFERs,26–44 so that if S w is known, then S s can be predicted for the various phases. The method is very general, because the phases include wet (water‐saturated) organic solvents, dry organic solvents, ionic liquids and aqueous biphasic systems.…”
Section: Methodsmentioning
confidence: 99%
“…The database has log K and log P values for solutes dissolved in 4-methyl-N-butylpyridinium tetrafluoroborate ([BMPy] For the analysis of data, we have modified the two linear free energy equations of the Abraham solvation parameter model [12][13][14][15][53][54][55][56] by rewriting each of the six solvent equation coefficients (e, s, a, b, V, and l) as a summation of their respective cation and anion contributions. Equations 4 and 6 apply to solute transfer between two condensed phases (i.e., log P), while eqs 5 and 7 involve solute transfer from the gas phase (i.e., log K).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In a number of cases, solvation of compounds in the dry and wet solvents is essentially the same, so that the same equations can be used to fit partition coefficients and to predict further partition coefficients into either wet or dry solvents. These solvents include hexadecane, 1, 2 olive oil, 1 the lower alkanes, 2 cyclohexane, 2 chloroform, 3 dodecane, 4 undecane, 4 isopropyl myristate, 5 butane,6 1,2-dichloroethane, 7 and the monohalobenzenes. 8 On the other hand, there are many solvents in which solvation of compounds into the wet or dry solvents is not the same, and different equations must be used for the correlation and prediction of partition coefficients in the wet and dry solvents.…”
Section: Introductionmentioning
confidence: 99%